2005
DOI: 10.1007/s10620-005-2462-7
|View full text |Cite
|
Sign up to set email alerts
|

Association Between 6-n-Propylthiouracil (PROP) Bitterness and Colonic Neoplasms

Abstract: Inadequate vegetable intake appears to increase colon cancer risk. Since genetic variation in taste influences vegetable preference, we tested associations between bitterness of 6-n-propylthiouracil (PROP), a measure of taste genetics, and number of colonic polyps, a measure of colon cancer risk, in 251 men who underwent screening lower endoscopy. Patients used the general Labeled Magnitude Scale to rate bitterness of 1.6 mg PROP delivered via filter paper. A subset of 86 patients reported weekly vegetable int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 46 publications
4
57
0
2
Order By: Relevance
“…These findings could have important health implications because many of the bitter-tasting compounds in foods (e.g., flavonoids, phenols, glucosinolates) are anticarcinogenic. Several studies in adults have also shown that PROP tasters consume fewer vegetables (45), and evidence in adults indicates higher incidence of colonic neoplasms in PROP tasters (11).…”
Section: Bitter-and Strong-tasting Foodsmentioning
confidence: 99%
“…These findings could have important health implications because many of the bitter-tasting compounds in foods (e.g., flavonoids, phenols, glucosinolates) are anticarcinogenic. Several studies in adults have also shown that PROP tasters consume fewer vegetables (45), and evidence in adults indicates higher incidence of colonic neoplasms in PROP tasters (11).…”
Section: Bitter-and Strong-tasting Foodsmentioning
confidence: 99%
“…Nontasters have shown an increased risk of alcoholism, 110 higher body mass index in women, 111 and dental caries in children, 112 while super taster males may have an increased risk of colon cancer. 113 Furthermore, the PROP-insensitive T allele (T785C) of TAS2R38 has been associated with eating behavior. Amish women with the T allele (T785C) reported higher disinhibition when eating behavior was assessed using the three-factor eating questionnaire.…”
Section: Genetic Chemosensory Variationmentioning
confidence: 99%
“…As a result, it can influence nutrition and potentially predispose individuals to certain diseases (e.g., 19). Thus, some taste receptor alleles can be disease risk factors.…”
Section: Practical Applications Of Taste Receptor Studiesmentioning
confidence: 99%